KESEHATAN IKAN NILA GIFT (Oreochromis niloticus) PADA USAHA KERAMBA DI DESA MASTA, TAPIN, KALIMANTAN SELATAN - Sarkiah sarkiah; Anny Rimalia; Rina Iskandar (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
This study aims to determine the health of Tilapia Gift and reared in cages and water quality conditions of the river masta as indicators of environmental health Masta river waters. The method used is a survey method, and analyzed by descriptive qualitative, Research results show that the health of tilapia gift that is maintained in the system of cages in the village of Masta is in good health and normal condition, wherein: hematocrit, ertitrosit, hemoglobin values, everything is in the range of normal values. Similarly, the results of water quality analysis, showed that the water quality parameter value, good temperature, pH, DO, and brightness in the normal range and within the limits tolerated by fish.